MEMBENTUK KEMBALI KOMISI KEBENARAN DAN REKONSILIASI DI INDONESIA - Nata, Reyhan Rezki; Husodo, Jadmiko Anam (Res Publica: Jurnal Hukum Kebijakan Publik, 2023)
The purpose of this legal research is to analyse the political law of Indonesia on settlement of serious human rights violations, especially with The Truth And Reconcilliation Commission. This research is a descriptive normative legal research type. Types of data consist of primary data and secondary data. Using primary data collection secondary data using literature study techniques. This research use the Qualitative data analysis techniques. A Truth and Reconciliation Commission shall be established to address impunity, break the cycle of violence, provide a forum for the parties of human rights violations to tell their story, get a clear accurate, clear and comprehensive picture of the past in order to facilitate genuine healing and reconciliation. The late progress of this commission, contributed directly or nondirectly to delayed our progress toward the bright future of this nation.